Awakening to Messiah a supernatural discovery of the Jewish Jesus. - Schneider, Rabbi K. A. (Shippensburg : Destiny Image, Inc., 2012)
Discover the Jewish Jesus! Teaching the Judaic roots of the Christian faith, fostering a deeper love for Yeshua, and sharing the Good News of Messiah with both Jew and Gentile. In Awakening to Messiah, Rabbi Kirt A. Schneider takes you on a personal journey, revealing how the Lord has appeared and has spoken to him over the past 30 years. You will vicariously experience some of the challenges he has faced as a Jewish believer in Messiah, including being kidnapped by a famous deprogrammer who hoped to destroy his faith in Jesus.</p.
Cover; Title; Copyright; Acknowledgments; Introduction; Chapter One: My Testimony; Chapter Two: Messiah in You-The Hope of Glory; Chapter Three: Experiencing the Peace of God; Chapter Four: God's Spirit in You; Chapter Five: Sharing Yeshua with Jewish People; Chapter Six: Witnessing Strategies; Chapter Seven: Conquering Theological Objections; Chapter Eight: Messianic Prophecy; About the Author.
Description based on print version record.
Keywords: Religion; Jesus Christ -- Messiahship; Messianic Judaism; Schneider, K. A., -- Rabbi; Christian converts from Judaism -- Biography; RELIGION / Christianity / Denominations; Electronic books